2022
DOI: 10.1186/s12876-022-02185-1
|View full text |Cite
|
Sign up to set email alerts
|

Administration of probiotics to healthy volunteers: effects on reactivity of intestinal mucosa and systemic leukocytes

Abstract: Background Oral administration of health-promoting bacteria is increasingly used in clinical practise. These bacteria have anti-inflammatory characteristics and modulate the immune system without major reported side effects. The mechanisms of action are not yet fully defined. Our aim was to study systemic effects of probiotics by measurements of leukocytes as well as local effects on rectal mucosal biopsies after adding a standardized inflammatory stimulus in vitro. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Several clinical trials reported improvement in halitosis, oral health, and related quality of life in subjects supplemented with different formulation of probiotics [ 65 , 66 , 67 , 68 , 69 ]. Moreover, many beneficial effects have been already demonstrated in the rebalance of the gut microbiota and also systemically [ 70 , 71 , 72 ]. Diverse Lactobacillus species exhibit immunomodulatory activities in the host gut, including enhanced antioxidant status and production of adhesion molecules and prevention of the establishment of neutrophil extracellular traps [ 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical trials reported improvement in halitosis, oral health, and related quality of life in subjects supplemented with different formulation of probiotics [ 65 , 66 , 67 , 68 , 69 ]. Moreover, many beneficial effects have been already demonstrated in the rebalance of the gut microbiota and also systemically [ 70 , 71 , 72 ]. Diverse Lactobacillus species exhibit immunomodulatory activities in the host gut, including enhanced antioxidant status and production of adhesion molecules and prevention of the establishment of neutrophil extracellular traps [ 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a healthy population, the use of probiotics can reduce systemic inflammatory responses ( Wang et al, 2022 ). In broilers infected with C. perfringens , the addition of Bacillus subtilis was effective in improving necrotizing intestinal lesions and regulating intestinal health ( Li et al, 2017 ; Stene et al, 2022 ). Lactobacillus casei was effective in suppressing Salmonella induced intestinal inflammation in chicks and improving intestinal mucosal immunity ( Cheng et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This significant decrease in inflammation was accompanied by a 50% decrease in the WBC count in the wound area [157]. Another study conducted on healthy individuals who were supplemented with Lactobacillus and Bifidobacterium probiotics for 6 weeks showed a decreased production of leukocytes (WBCs) and proinflammatory cytokines (IL-6 and TNF-α), showing the important role of probiotics in maintaining healthy intestinal homeostasis [158].…”
Section: White Blood Cell (Wbc) Countmentioning
confidence: 95%